Varicella Zoster Virus-Associated Meningitis as a Rebound Varicella Zoster Disease after Antiviral Discontinuation - Tetsuko Sato; Takenobu Yamamoto; Yumi Aoyama (Case Reports in Dermatology, 2021)
Varicella zoster virus (VZV)-associated meningitis is usually progressive and can be fatal, and early diagnosis and aggressive treatment with intravenous antivirals such as acyclovir (ACV) are required in immunocompromised patients. Patients receiving corticosteroids and immunosuppressive therapy have a significantly higher risk of VZV-associated meningitis. In this report, we describe an unusual case of herpes zoster (HZ) in a young woman who was first diagnosed during tapering of prednisone for dermatomyositis. The skin lesions affected the left L2 and L3 dermatomes, which is unusual in VZV-associated meningitis. Despite showing a good rapid response to antivirals, she developed VZV-associated meningitis immediately after discontinuation of ACV. This phenomenon is often called rebound VZV reactivation disease and occurs after discontinuation of antivirals. This case was notable in that the affected dermatomes were distant from the cranial nerves. Thus, progression of HZ to VZV reactivation-associated meningitis can occur even in appropriately treated HZ patients. Continuation of antivirals beyond 1 week in patients on immunosuppressive therapy may be associated with a decreased risk of severe rebound VZV disease, such as VZV-associated meningitis.